공원이용자의 설계개념과 설계전략에 대한 인식이 공원 만족도에 미치는 영향 - 광교신도시의 근린공원을 대상으로 - 장재호; Jang Jae-ho; 김단영; Kim Dan-young; 신민지; Shin Min-ji; 신지훈; Shin Ji-hoon (한국조경학회지, 2017)
본 연구는 광교신도시의 도시공원을 대상으로, 공원이용자들의 설계개념 인지정도와 설계개념이 적용된 공간에 대한 만족도를 조사하고, 설계개념이 만족도에 미치는 영향을 분석하고자 하였다. 이에 센트럴마운틴공원과 호수공원을 대상으로 이용자의 특성, 공원시설에 대한 중요도-만족도, 공원의 선호도-만족도를 분석하였다. 본 연구에서 도출한 연구결과를 요약하면 다음과 같다. 첫째, 공원이용자의 특성을 분석한 결과, 두 공원 모두 일반적으로 가족단위의 이용객이 많았다. 둘째, 산책로가 시설의 중요도와 만족도에서 가장 높은 평가를 받았다. 셋째, 두 공원 전반적인 만족도는 모두 높게 나타났으나, 공원이용자들의 설계인식과 유의한 관계가 나타나지 않았다. 넷째, 공원이용자의 공간별 인식정도와 만족도를 분석한 결과, 두 공원의 설계개념과 설계전략에 대한 인식은 5점 리커드 척도에서 평균 3점 이상으로 높은 정도를 보였다. 하지만, 이용자의 인식정도와 공간별 만족도는 유의한 관계라고 정의하기는 어려웠다. 따라서 본 연구를 통해서 공원이용에 있어 전반적인 만족도에는 설계인식에 대한 인지정도가 거의 영향을 미치지 않는다는 것을 확인할 수 있었다. 오히려 공간에 대한 이용자의 개인적인 선호도와 만족도가 더 큰 영향을 미친다는 것을 알 수 있었다. 반면, 조사대상지의 계절별 조사가 미흡했다는 점과 대상지가 좀 더 다양하지 못한 한계성을 가지고 있으나, 도시공원의 대표공원이라 할 수 있는 근린공원과 수변공원을 대상으로 공원이용자의 만족도에 설계자의 설계개념과 설계전략이 어느 정도 영향을 미치는지 조사하였다는 점에서 의의가 있다. The purpose of this study is analyze the impact on users` cognition of design concept, satisfaction of design concept, adapted park space, and effect of design concepts on park use satisfaction. The study sites are Central Mountain Park and Lake Park in Gwanggyo New Town, Suwon. We analyzed importance-satisfaction of park facilities in the park and preference-satisfaction of park. The results of this study are as follows. First, generally users visit the park as a family unit. Second, trails got high scores in importance-satisfaction of park facilities. Third, park users` satisfaction received a high score generally, but it doesn`t show statistic significance with users` cognition of design concept. Fourth, cognition of the two parks` design concept and design strategy got a high score - over three points on average - based on the 5 - point Likert scale. However, upon analysis of users` cognition of design concept and satisfaction of design concept adapted park space, there is no statistic significance. Therefore, we noticed that the park`s design concept had an effect on park users` satisfaction; rather, personal preference and satisfaction of users had more impact on satisfaction. On the other hand, this study was limited in that we didn`t survey across all four seasons and had few target areas. But it has some significance in that we used a visual documentation, attaching existing photos including design concept, to increase users` understanding. Also, we directly asked about the parks` user design concept and strategy.